PRELIMINARY PHYTOCHEMICAL SCREENING OF ACACIA CAESIA (L.) WILLD. - DR. C. ARUNA (International Journal of Pharma and Bio Sciences, 2014)
Plant kingdom is a treasure house of potential drugs. The drugs from plants are easily available , less expensive, efficient and without side-effects. Medicinal plants contain some natural products which perform definite physiological action on the human body. These products are called phytochemicals which are synthesized primary or rather secondary metabolism of plants . Secondary metabolites are of major interest because of their biological activities ranges from antimicrobial, antibiotic, insecticidal and hormonal properties which are highly important in pharmacological and pharmaceutical activities. To find out phytochemical constituents in the Acacia caesia plant, the plant parts were collected at Mallemadugu dam of chittoor district, Andhra Pradesh. They were shadow dried and extracted with methanol, petroleum ether and water. Phytochemical screening was carried out according to Standard procedures. Phenols, flavonoids, terpenoids, carbohydrates, proteins, reducing sugars, Anthocyanidins, tannins, lignins and indoles were found to be present in the extracts.